Emerging Role of the Band‐Structure Approach in Biohybrid Photovoltaics: A Path Beyond Bioelectrochemistry. (18th December 2017) - Ravi, Sai Kishore; Udayagiri, Vishnu Saran; Suresh, Lakshmi; Tan, Swee Ching
Abstract: Emulation of natural photosynthesis is central to modern photovoltaic research targeting sustainable and economic ways of solar energy harvesting. Natural photosynthetic systems have succeeded in efficiently harvesting solar energy which is key to the sustenance of life on earth. With numerous advances in understanding the structure and function of the natural photosystems, the last decade has witnessed new perspectives in developing bioinspired photovoltaics. Interestingly, organic photovoltaics (OPVs) adopting photosynthetic design principles and biophotovoltaics (BPVs) adopting solid‐state device architectures have now converged at a juncture. Several reports in recent years point to a new scope of improvement in OPVs and BPVs stemming from mutual inspiration. At this juncture, there are new perspectives by which a BPV can be designed that were previously limited only to conventional optoelectronics. Treating natural pigment–proteins as optically and electronically functional materials in any photovoltaic design, from the band‐theory viewpoint, is a promising direction for advancing BPVs beyond the boundaries of bioelectrochemistry. This article presents an overview of selected reports on BPVs in the last few years utilizing new design concepts based on band‐theory and its associated principles. In light of this, the scope of the band‐structure approach in BPVs is discussed, eliciting prospective research directions. Abstract : The electronic processes in natural photosynthetic systems are reviewed, and a contrast is established with emerging photovoltaic systems, thereby providing insight on how the band‐structure approach can aid in bridging photosynthetic research and emerging photovoltaic technologies by mutual inspiration.